An Experience in Laboratory Diagnosis of Fungal Infections in COVID -19 Patients - Boorgula, Sushma Yadav; Yelamanchili, Sadhana; Sistla, Srinivas Kishore; Saher, Lubna; Gujjarlapudi, Deepika; E., Shalini; V., Sindhu Devi; Duvvur, Nageshwar Reddy (International Archives of Otorhinolaryngology, 2023)
Introduction Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has cast a gloom spell on healthcare worldwide, infecting millions of people.Objective The aim of the present study is to determine the prevalence and review the contributing comorbidities and the precipitating factors leading to the emergence of the fungal infections in COVID-19-affected patients. To assess the utility of different laboratory techniques for confirmation of fungal infections. To assess the strengths and limitations of the diagnostic methods.Methods We have studied 252 clinical samples obtained from 121 COVID-positive patients.Results Among the 121 patients clinically diagnosed with fungal infections, 88 had diabetes and were given steroids for treatment (p-value = 0.001). Ninety-five patients (78.5%) had a positive laboratory diagnosis (either culture positive, potassium hydroxide [KOH]-positive or positive histopathology report). Fungal culture was positive in 75 (61.9%) patients and histopathology report was positive in 62 (51.2%). Histopathology was positive in 7 (5.8%) patients in whom culture and KOH were negative.Conclusion Aggressive treatment methods, administration of immune suppressants, and antibiotics, with an intention to salvage, have made patients susceptible to the benign fungus, causing it to evade the host immunity, thus leading to invasive infections. Applying different laboratory modalities would not only aid in providing fast and valuable information but also help in understanding the pathology which would assist the clinician in selecting the correct treatment for the patient.
Keywords: COVID-19; sars-cov-2; diabetes mellitus; steroids; fungus